PENGARUH PROGRAM PENDIDIKAN PELATIHAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA TENAGA PENYULUH KELUARGA BERENCANA (KB) DI PROVINSI RIAU (STUDI KASUS PADA KABUPATEN PELALAWAN, KABUPATEN SIAK DAN KABUPATEN INDRAGIRI HULU) - Desy Wulandari; Susi Hendriani; Machasin Machasin (Jurnal Ekonomi, 2014)
The objective of this research is to analize the effect of the education and trainingprogramm, motivation dan job environment again the performance offieldworkers for family planning in Riau Province. This research takes 3 sampleof regency, that they are Pelalawan Regency, Siak Regency and Indragiri HuluRegency. The result of the research indicates that the education and trainingprogramm, motivation and job environment have the effect again the performanceof fieldworkers of family planning in Riau Province together. It’s indicated byFratio (25,491) > Ftable (3,100) on significant α = 5%. The formula of the multiplelinear regression is : Y   X  X  X  e 1 2 3 20,467 0,349 0,152 0,060From above formula we can see that the regression coeffisien for threeindependent variables have a positive effect again dependent variables(perfrmance of fieldworkers of family planning in Riau Province). The number ofeffect contributed by the education and training programm, motivation and jobenvironment again the performance of fieldworkers of family planning in RiauProvince can be seen from determinated coefficient (R2) and the figure is 0,465 or45,5%. While closed relationship between independent variables and dependentvariable is indicated by the figure coefficient correlation (R) is 0,682. The parcialtest indicated that the biggest tratio is found on variable the education andtraining programm (X1) the tratio = 4,598 > ttabel = 1,662 with the r2 = 44,0%. Thisresult indicates that the education and training programm has the main factoragain performance of fieldworkers of family planning in Riau Province.